2016
DOI: 10.1093/hmg/ddw395
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin is a scaffolding protein in the ATM oxidative DNA damage response complex

Abstract: Huntington's disease (HD) is an age-dependent neurodegenerative disease. DNA repair pathways have recently been implicated as the most predominant modifiers of age of onset in HD patients. We report that endogenous huntingtin protein directly participates in oxidative DNA damage repair. Using novel chromobodies to detect endogenous human huntingtin in live cells, we show that localization of huntingtin to DNA damage sites is dependent on the kinase activity of ataxia telangiectasia mutated (ATM) protein. Super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(136 citation statements)
references
References 52 publications
6
122
0
Order By: Relevance
“…Recently, it was demonstrated in a cell culture model that N17-phosphorylated HTT is found at sites of DNA damage in the nucleus, where it co-localizes with ATM to participate in the base excision repair pathway, and this co-localization is dependent on ATM kinase activity [50]. Furthermore, HTT also exhibits an oxidative stress-dependent interaction with other DNA repair proteins such as XRCC1, Flap structure-specific endonuclease 1 (FEN1), APE1, and high mobility group box 1 (HMGB1) [50]. …”
Section: Htt In Stress Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was demonstrated in a cell culture model that N17-phosphorylated HTT is found at sites of DNA damage in the nucleus, where it co-localizes with ATM to participate in the base excision repair pathway, and this co-localization is dependent on ATM kinase activity [50]. Furthermore, HTT also exhibits an oxidative stress-dependent interaction with other DNA repair proteins such as XRCC1, Flap structure-specific endonuclease 1 (FEN1), APE1, and high mobility group box 1 (HMGB1) [50]. …”
Section: Htt In Stress Responsesmentioning
confidence: 99%
“…When ROS stress is relieved, de-phosphorylation of S13 and S16 occurs, and HTT translocates back into the cytoplasm by a CRM1-dependent nuclear export mechanism [56]. Oxidative stress and ROS cause DNA damage, and the nuclear entry of N17-phosphorylated HTT allows it to participate with ATM in DNA base excision repair [50]. …”
Section: Htt In Stress Responsesmentioning
confidence: 99%
“…I note that a recent study investigating the consequence of Htt inactivation in the brains of adult mice also did not detect significant changes in LC3 or p62 protein levels [147]. Because stress can induce selective macroautophagy [57], and recent in vitro studies have identified N17 domain-dependent roles for HTT in cellular stress and DNA damage responses [60,82,114,116], it is possible that the contribution of the HTT N-terminus in these pathways may not be apparent until homeostasis is perturbed, such as under chronic stress. For example, the expression of 140Q-Htt was needed to elicit more robust autophagy phenotypes in Htt 140Q/ΔQ mice [110].…”
Section: Discussionmentioning
confidence: 96%
“…HTT is a scaffolding protein that is involved in multiple cellular functions [65,81,82]. The generation and characterization of Htt knock-out mice revealed that Htt has an essential function during early embryonic development [83][84][85].…”
Section: Wild Type Huntington Functionsmentioning
confidence: 99%
See 1 more Smart Citation